Efektivitas Penyuluhan Berbasis Power Point terhadap Tingkat Pengetahuan, Sikap, dan perilaku tentang pencegahan Cacingan pada Siswa kelas V dan VI SDN 01 Kromengan Kabupaten Malang - Ramadhani, Suci Nur; Adi, Sapto; Gayatri, Rara Warih (Preventia: The Indonesian Journal of Public Health, 2020)
The results of the Health Department survey in 2013 prevalence of worms transmitted through soil in primary school (SD) reached 28.12%, with details of 60% of students infected with roundworms; 16% of students were infected with whipworms; and 7% of students were infected by hookworm. The prevalence of worms in SDN 01 Kromengan became the highest compared to other schools in Malang Regency, which reached 48%. To reduce the prevalence of intestinal worms, do counseling using power point media. This study aims to determine the influence of counseling using power point media to the level of knowledge, attitude, and behavior of students of grade 5 and 6 SDN 01 Kromengan. This research is quasi experimental with pretest-postest group design method. With the subjects of 42 students using the total sampling, conducted in SDN 01 Kromengan Malang Regency, and conducted in April-May 2017. This study used a questionnaire distributed directly to students. Data analysis using paired t-test with significant level of 0.05. Based on the result of the research, it shows that there is a difference between pretest-posttest with t-count of knowledge (-10,094), attitude (-7,658), and behavior (-8,762)